The East–West Dichotomy from the Perspectives of Comparative Civilization Studies - Andrijauskas, Antanas (Acta Orientalia Vilnensia, 2000)
The present article is devoted to the critical analysis of dichotomical conceptions of relations between civilizations East and West. The deconstruction of the main concepts of Western philosophy of culture breaks the narrow borders of the rationalistic metaphysics and opens new methodological perspectives to the comparative culturology. Inquiring to the “marginal” cultures of the World and treating their symbols and forms as equal to those of the “central”, i.e. of the Eastern and Western cultures the postmodern comparativism looks for more complex model of civilization. The latter have to replace the traditional one, which seems too simple, for it overestimates the East and West dimension.